2019
DOI: 10.4067/s0717-95022019000100212
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Immunohistochemical Effects of Neuroectodermal Cells Transplantation After Spinal Cord Injury in Rats

Abstract: In spinal cord injury, radical treatment is still a persistent hope for patients and clinicians. Our study aimed to determine the different histological changes in central, cranial and caudal sites of compressed spinal cord as a result of neuroectodermal stem cells (NESCs) transplantation in rats. For extraction of NESCs, future brains were extracted from mice embryos (10-days old) and cultured. Eighty, male rats were divided randomly into control, sham (20 rats each); while 40 rats were subjected to compresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Regarding to the histological and immunohistochemical examination, control group revealed permanent degenerative changes. These changes were similar to previously reported in rats by (Othman, 2017;AL-Karim et al, 2019).…”
Section: Immunohistochemistrysupporting
confidence: 93%
See 3 more Smart Citations
“…Regarding to the histological and immunohistochemical examination, control group revealed permanent degenerative changes. These changes were similar to previously reported in rats by (Othman, 2017;AL-Karim et al, 2019).…”
Section: Immunohistochemistrysupporting
confidence: 93%
“…Similar results were reported previously in rats (Chen et al, 2018), while in BM-MSCs, transplantation of BM-MSCs showed few reactive astrocytes cranial and caudal to the center of the injury because the BM-MSCS had the ability to reduce astrocytes response. These results were similar to that found in rats by (Al-Karim et al, 2019).…”
Section: Immunohistochemistrysupporting
confidence: 92%
See 2 more Smart Citations